Penerapan Media Audiovisual untuk Meningkatkan Hasil Belajar Peserta Didik Kelas III SDN 1 Hadiluwih - Anjarwati, Yuni; Musidik, Elly's Mersina; Yuniarsih, Etik Lestari (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Based on the results of observations made at SDN 1 Hadiluwih Kec. Ngadirojo, Kab. Pacitan. The learning activities carried out are less effective, this is due to the learning activities caused by the learning method which is still monotonous with lectures without using the media as a supporting tool. This type of research is Classroom Action Research (PTK) and this research is in collaboration with tutor teachers as well as homeroom teachers for class III SDN 1 Hadiluwih. The subjects in this study were class III students at SDN 1 Hadilwuih Kec. Ngadirojo, Kab. Pacitan. Data collection techniques consisted of observation and posttest questions and there were four stages in the research conducted, namely planning, implementing, observing and reflecting. The above problems lead to the need for creative and innovative learning media to improve student learning outcomes. Learning media that is easy and can be created by educators is audiovisual media which is able to have a big influence on learning activities. This makes students experience lagging behind and has an impact on the learning outcomes of students, the majority of whose learning outcomes are under the KKM. The results of the data from pre-cycle with KKM 75, only 30.76% of students who can fulfill the achievement of mastery. In Cycle I there was an increase in students' learning achievement which reached 53.84%. The percentage almost reached the expected target even though there were several points that students had not understood. In cycle II 84.61% The percentage obtained has reached the expected target. The results of this study indicate that there is an increase in learning activities using audiovisual media.